Persepsi Masyarakat Terhadap Profesionalisme Dan Kepatuhan Dalam Penegakan Hukum Oleh Polisi - Nurwandri, Andri; Syam, Nur Fadhilah; Arifin, Muhammad Hasnanul; Siregar, Muhammad Syafii Arrazaq; Dasopang, Mara Ihklas; Priantika, Novi; Pradana, Indra (CV. Pusdikra Mitra Jaya, 2023)
Acts of violence are often carried out by the police during the investigation process with the aim of obtaining a confession from the suspect. This phenomenon has become a common occurrence, which has been revealed through various studies. The causes include a lack of investigative supervisory institutions, a lack of legal instruments, protection from institutions, and an unprofessional attitude on the part of the police. This situation means that suspects do not have the opportunity to defend their rights, while perpetrators of violence remain unsanctioned. Professionalism is related to moral issues that are integrated into the code of ethics, and violations of the code of ethics indicate the existence of moral problems within the police force. Moral improvement among investigators is needed so that the investigation process can run well and in line with expectations.